Geodynamics of Alpine Belt and Caribbean Region: Plate - Tectonics and Plume - Tectonics - Svalova, Valentina (Journal of Basic & Applied Sciences, 2022)
The origin and evolution of geological structures reflect lithosphere-asthenosphere interaction in the process of lithospheric plate movement. Mantle diapirs contribute significantly to the sedimentary basins formation in Alpine belt and Caribbean region. Mantle diapirs are the result of density inversion in the asthenosphere–lithosphere system in the periods of tectonomagmatic activations. Increasing heat flow and mantle diapirs on the phone of convergence of Africa and Eurasia in Alpine belt and North and South Americas in Caribbean region produce intercontinental seas in the Cenozoic. The analytical solution of the problem give possibility to find the critical parameters connecting the mantle flow dynamics with surface relief evolution. In Alpine belt, the mantle diapirs form new basins at the final stage of Africa–Eurasia collision in the Cenozoic. In the Caribbean region, great mantle diapir separates the North and South Americas in the Mesozoic, and then the diapir is the source for different smaller diapirs during the convergence of these continents in the Cenozoic. The Gulf of Mexico and Pre-Caspian Depression are connected with mantle diapirs upwelling and have common geological-geophysical features as very rich oil-gas and salt bearing structures. Geodynamics of Alpine belt and the Caribbean region is determined by plume - tectonics on background of plate - tectonics in these regions.